Cash holdings and relationship lending - Dahiya, Sandeep; Hallak, Issam; Matthys, Thomas (Journal of Corporate Finance, 2025)
We examine the effect of relationship lending on a firm’s cash-holding levels. Relationship lending allows lenders to generate private information about borrowers, which mitigates their financial constraints. Using exogenous shocks to identify stress to lending relationships, we show that strong lending relationships translate into lower cash holding for borrowers. We also show that the impact of lending relationships on cash holdings is greatest for firms faced with high information asymmetry. Thus, opaque firms are more likely to use their borrowing relationship as a substitute for cash holdings. We find that relationships have a negative impact on the market value through a firms’ level of cash holding. This impact is significantly greater when firms experience a large change in their cash holdings.